Genetic determinants of heart failure: facts and numbers. (19th February 2018) - Czepluch, Frauke S.; Wollnik, Bernd; Hasenfuß, Gerd
Abstract: The relevance of gene mutations leading to heart diseases and hence heart failure has become evident. The risk for and the course of heart failure depends on genomic variants and mutations underlying the so‐called genetic predisposition. Genetic contribution to heart failure is highly heterogenous and complex. For any patient with a likely inherited heart failure syndrome, genetic counselling is recommended and important. In the last few years, novel sequencing technologies (named next‐generation sequencing – NGS) have dramatically improved the availability of molecular testing, the efficiency of genetic analyses, and moreover reduced the cost for genetic testing. Due to this development, genetic testing has become increasingly accessible and NGS‐based sequencing is now applied in clinical routine diagnostics. One of the most common reasons of heart failure are cardiomyopathies such as the dilated or the hypertrophic cardiomyopathy. Nearly 100 disease‐associated genes have been identified for cardiomyopathies. The knowledge of a pathogenic mutation can be used for genetic counselling, risk and prognosis determination, therapy guidance and hence for a more effective treatment. Besides, family cascade screening for a known familial, pathogenic mutation can lead to an early diagnosis in affected individuals. At that timepoint, a preventative intervention could be used to avoid or delay disease onset or delay disease progression. Understanding the cellular basis of genetic heart failure syndromes in more detail may provide new insights into the molecular biology of physiological and impaired cardiac (cell) function. As our understanding of the molecular and genetic pathophysiology of heart failure will increase, this might help to identify novel therapeutic targets and may lead to the development of new and specific treatment options in patients with heart failure.